Traditional Plants Used for the Treatment of Ear Problems in Beed District of Maharashtra - and S. K. Markandeya, B. W. Chavre*, B.Y. Patil, D.S. Jadhav (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The present paper focuses on the botanicals used in the treatment of of ear problems in Beed District of Maharashtra. The author gathered important information of such a 10 plants belonging to 08 different families. An ethnobotanica! Survey was carried out in the district and information was collected about the plants, which are used to cure different problems of Ear like Earache, Pus Formation in the ear, listening problem etc. All the species included in this paper are wildly grown. This traditional knowledge is very valuable source for the further research and discovery of new pharmaceutical drugs. For each plant species scientific name, family, local name, parts used and mode of administration for the treatment of ear problem are provided.